A welcome wasp's nest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Interactive catalogue of world Chalcidoidea 2001 By John S Noyes, Taxapad 2001. CD Rom for Windows 95, 98, 2000, NT & XP US$ 190 Euro 184.50